Status quo and utilization trend of global helium resources - Cao, Qian; Li, Ying; Fang, Chaohe; Liu, Renhe; Xiao, Hongping; Wang, Shejiao (Frontiers in Environmental Science, 2022)
Helium, as an important strategic resource, is widely used in medical and sophisticated high-tech, but its distribution is seriously imbalanced, mainly concentrated in the USA, Qatar, Algeria and Russia. In this paper, based on the systematic study of the global distribution and supply and demand of helium, the current situation and future trend of helium consumption in china were analyzed. In view of the shortage of helium resources in China and the high dependence on foreign countries, suggestions were put forward to strengthen the comprehensive research on domestic helium resources, enhance the investigation and utilization of associated helium resources, deepen the research on helium exploration and development technology, and promote the process of commercial exploration and development.